2013
DOI: 10.9790/1684-0722836
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Analysis of Steam Turbine Power Plants

Abstract: Steam are a major energy consumer. Optimising process operating conditions can considerably improve turbine water rate, which in turn will significantly reduce energy requirement. Various operating parameters affect condensing and back pressure turbine steam consumption and efficiency. The industrial sector is the largest energy consumer, accounting for about 30 % of total energy used. Fuel and energy prices are continuously rising. With the present trend of energy prices and scarcity of hydrocarbon resources … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…From the data, it is observed that SG flow between 6 and 7 Mw import is falling below the threshold value of 320 Mt/h. Utilizing Newton Raphson's empirical formula [10], the BEP is obtained.…”
Section: Mathematical Modeling Results To Estimate Bepmentioning
confidence: 99%
See 3 more Smart Citations
“…From the data, it is observed that SG flow between 6 and 7 Mw import is falling below the threshold value of 320 Mt/h. Utilizing Newton Raphson's empirical formula [10], the BEP is obtained.…”
Section: Mathematical Modeling Results To Estimate Bepmentioning
confidence: 99%
“…Based on the solar radiation per day, the DC power generated from the PV system can be estimated. The DC power generated mainly depends on different factors, including PV peak power at standard test conditions of (STC), solar radiation, and cell temperature and is represented by Equation (10).…”
Section: Pv Output Power Estimation Using Ghi/gtimentioning
confidence: 99%
See 2 more Smart Citations